AB0764 An Onset of Psoriasis after 40 Years and A Low Education Level May PREDICT the Development of Diabetes Mellitus in Psoriatic Arthritis. (10th June 2014) - Queiro, R.; Rodríguez, S.; Acasuso, B.; Morante, I.; Cabezas, I.; Coto, P.; Alperi, M.; Ballina, J.
Abstract : Background: Psoriasis and psoriatic arthritis (PsA) have been associated with an increased risk of cardiovascular morbidity. One of the main factors that may explain this fact is the higher prevalence of type II DM in these populations. Recent meta-analyses suggest that the risk of type II DM is higher among patients with PsA compared to those who only show psoriasis 1 . The clinical features of patients with PsA who develop DM are not well defined, and those disease factors which may predict the development of this complication are also unknown. Objectives: The purpose of this study was to analyze the demographic and clinical characteristics of patients with PsA who develop DM and determine which factors linked to the disease may act as predictors of DM. Methods: Retrospective cohort study conducted in a single university hospital that included 206 Spanish patients diagnosed of PsA according to the CASPAR criteria. The average age was 53±13 years, the age of onset of psoriasis 30.5±17 years, and that of arthritis was 43.3±14.2 years. The average duration of arthritis was 18±11.6 years. The interval between the onset of psoriasis and arthritis was 14.6±12.6 years. There were 113 males and 93 females. DM was diagnosed according to international standard definitions. Univariate and multivariate analyses were used to investigate those factors associated to DM risk. Results: Twenty-six of 206 patients had type II DM (12.6%). Compared with patients who did not develop DM, subjects with type II DM had onset ages of psoriasis (46±15 yr. vs. 28.3±16.3 yr.) and arthritis (51±13.9 yr. vs. 42.3±14 yr.) significantly higher. There was no difference in the prevalence of DM between men and women. Patients with DM also had higher prevalence of hypertension (84% vs. 23.3%, p<0.0001), dyslipidemia (60% vs. 26.7%, p=0.001), obesity (63.7% vs. 32.2%, p=0.009), coronary heart disease (20% vs. 2.2%, p=0.0001), cerebrovascular disease (24% vs. 1.7%, p=0.0001), and peripheral vascular disease (12% vs. 1.7%, p=0.004). However, the proportion of smoker was lower among DM patients (17.4% vs. 31.2%). Among patients with DM, there was a higher percentage with primary education compared to patients without DM (85.7% vs. 47.9%, p=0.005). The proportion of subjects with polyarthritis (56% vs. 32%, p=0.020) and pustular psoriasis (16% vs. 3.3%, p=0.006) was also higher among this subpopulation. Regardless of age, sex, systemic medications, and other confounding variables, the predictors of DM in this population with PsA were the age of onset of psoriasis over 40 years (OR 11.5, 95%CI: 2.24-59.4, p=0.003) and a low education level (OR 9.15, 95%CI: 1.05-79.4, p=0.045). Conclusions: the prevalence of DM in this PsA population is similar to that published in other series. Patients with DM also had a higher burden of adverse cardiovascular outcomes. Moreover, patients with older ages at onset of psoriasis and lower education levels seem to be at higher risk for developing this complication. References: Psoriasis, psoriatic arthritis and type 2 diabetes mellitus: a systematic review and meta-analysis. Coto-Segura P, Eiris-Salvado N, González-Lara L, Queiro-Silva R, Martinez-Camblor P, Maldonado-Seral C, et al. Br J Dermatol. 2013 Oct;169(4):783-93 Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.2056